Clean Air and Healthy Lungs : Enhancing the World Bank's Approach to Air Quality Management - Awe, Yewande; Nygard, Jostein; Larssen, Steinar; Lee, Heejoo; Dulal, Hari; Kanakia, Rahul (World Bank, Washington, DC, 2015)
This report specifically deals with air pollution, which was reported, by the World Health Organization (WHO), as the single largest environmental health risk globally in 2012 (WHO, 2014a). Air pollution from outdoor and household sources jointly account for more than 7 million deaths (3.7 million from ambient air pollution and 4.3 million from household air pollution). The following sections of this chapter present the objectives of, and key aspects of the institutional context for, this report followed by an examination of some of the major drivers of deteriorating ambient air quality in developing countries; air pollution sources and impacts; and the status of air quality management in developing countries. Chapter two presents the results of a desk-based portfolio review of World Bank projects that are relevant to reduction of air pollution. This is followed, in chapter three, by an examination of case studies of World Bank projects whose objectives include addressing ambient air pollution, highlighting good practices and lessons for future work of the Bank in supporting clients. Chapter four presents possible approaches for enhancing future Bank support in helping clients to improve air quality and reduce the associated adverse health outcomes. Chapter five presents overall conclusions and recommendations.